An Assessment of Professional Quality of Life and Experience With Critical Incidents Among OBGYN Residents. (October 2016) - Black, Jonathan; Cutler, Abigail; Pathy, Shefali; Sheth, Sangini
Abstract : BACKGROUND: Residents are exposed to a variety of clinical experiences that trigger wide-ranging emotions and, in severe cases, cause significant psychological distress. METHODS: OB/GYN residents were asked to complete an anonymous survey consisting of a validated Professional Quality of Life Scale (ProQOL) and additional questions related to their experience with critical incidents (CI) and debriefing. ProQOL (maximum score of 50) measures three constructs: Compassion Satisfaction, Secondary Trauma Stress, and Burnout; each is scored separately and correlated to a low-average-high scale. RESULTS: Response rate was 83% (25/30). Mean ProQOL scores correlated with an average level of compassion satisfaction (39.8±6.3), a low level of secondary trauma stress (22±4.8), and an average level of burnout (25.6±5.4). The majority of residents (68%) experienced a CI; 70% reported two or more. Among those involved in a CI, 53% reported never having debriefed and 82% felt they never or only sometimes received adequate support to process such events. All residents experiencing a CI felt the event(s) at least sometimes changed their clinical practice. Most residents (88%) believe post-incident debriefing sessions would be helpful. DISCUSSION: At our institution, OB/GYN residents experience an average professional quality of life. Furthermore, residents commonly experience CI but have little opportunity to debrief. Additional work is needed to better understand the professional quality of life of OB/GYN residents nationwide and how they react to and cope with critical incidents.